Challenges to Humanism in the Context of Modern Hybrid Wars - Yevheniia Levcheniuk; Vitalii Turenko (International Society of Philosophy and Cosmology, 2024)
Currently, there are a significant number of international treaties aimed at protecting human rights and international humanitarian law, which aim to reduce the suffering of civilians in conflicts. However, in reality, their implementation and effectiveness can vary significantly depending on the political will of countries, the intervention of third-party forces, and the complexity of the conflicts themselves. In particular, international law often faces implementation difficulties and states' disregard for their obligations. The aggression of authoritarian regimes and massive human rights violations may remain outside the influence of international norms and standards due to the lack of international consolidation or political dependence. Thus, although international treaties are designed to protect human rights, reality shows that their impact may be limited, especially in the context of global conflicts, hybrid confrontations, etc.